Persepsi Masyarakat Terhadap Kawasan Industri Di Kecamatan Bergas Dalam Perubahan Kondisi Sosial-Ekonomi Dan Lingkungan - Iqbal Sadri; Mohammad Muktiali (Teknik PWK (Perencanaan Wilayah Kota), 2019)
This research is based on the rapid development of the industrial sector in Bergas district, this district has the largest industries in Semarang Regency, based on Disperindag data there is about 82 of industries. This study aims to determine the impact of the existence of industrial area on changing social economy conditions and environment especially in Bergas District. This research uses quantitative descriptive analysis method. The results of this study are that there is an influence on increasing employment opportunities and increasing income, which is directly proportional to the increase in education and ownership of living facilities. The impact of the industry on increasing pollution, they are water, air and noise pollution, found that as many as 98% of the people in the study area did not feel water pollution and 2% felt there was water pollution. Then for air pollution 57% do not feel air pollution while 43% feel there is air pollution. While for noise as much as 57% did not feel noise and 43% felt that there was industrial noise, the increase in disease did not have much impact.